Hydraulic Conductivity Modeling of Fractured Rock at Grasberg Surface Mine, Papua-Indonesia - Cahyadi, Tedy Agung; Widodo, Lilik Eko; Syihab, Zuher; Notosiswoyo, Sudarto; Widijanto, Eman (ITB Journal Publisher, LPPM ITB, 2017)
Packer tests and slug tests were conducted at 49 points at the Grasberg surface mine, Indonesia to obtain hydraulic conductivity data. The HC-system approach, which relies on rock quality designation, lithology permeability index, depth index, and gouge content designation, was applied. Geotechnical drill holes in 441 locations, consisting of 4,850 points of information, were used to determine the K values using the equation K = 2x10-6x HC0.5571. The K values, which were within the range of 10-8 and 10-5 m/s, were distributed into five alternative 3D distributions using Ordinary Kriging (OK) and Artificial Neural Network (ANN). The result of the ANN modeling showed that some of the K values, with log K varying from -10.51 m/s to -3.09 m/s, were outside the range of the observed K values. The OK modeling results of K values, with log K varying from -8.12 m/s to -5.75 m/s, were within the range of the observed K values. The ANN modeled K values were slightly more varied than the OK modeled values. The result of an alternative OK modeling was chosen to represent the existing data population of flow media because it fits well to the geological conditions.